Influência de diferentes teores de Cu e Cr na solidificação e microestruturas de ligas fundidas hipoeutéticas Al-Cu-Cr - Elesbão, Denis Silva Grillo (2023)
The present work investigates the influence of different Cu-Cr ratios on the solidification path and microstructure formation in as-cast hypoeutectic Al-(2.5, 3.5, 4.5) Cu alloys with additions of 0.25 and 0.50 Cr (mass%). The alloys were prepared by melting pure aluminum, electrolytic copper, and pure chromium. Thermal analyses based on cooling curves were carried out to determine the solidification intervals and transformation temperatures of each alloy with low and moderate cooling rates. Comparisons with data obtained from both differential thermal analyses (DTA) and simulations using the Thermo-Calc thermodynamics software were done. Samples were taken from the solidified ingots, subjected to metallographic analysis (optical - OM and scanning electron - SEM microscopies), X-ray diffraction (XRD) analyses and Vickers microhardness (HV) measurements. The thermal analyses showed that the Liquidus and Solidus temperatures were practically unaffected by the range of cooling rates investigated in this work. The microstructural analyses revealed that Cr additions refined the microstructure when compared to the binary Al-Cu alloys. SEM with semi-quantitative EDS (energy-dispersive X-ray spectroscopy) analyses permitted to identify the presence of the CuAl2 intermetallic compound, AlCuCrFe precipitates, and some dispersed needle-like Al-Fe particles in all samples. The XRD analyses confirmed peaks of the α-Al (cubic, matrix) and CuAl2 (tetragonal, interdendritic) phases. Additional peaks were undetected due to their small presence in the investigated alloys. As the alloy Cu and Cr contents increased, microhardness values increased